Impact of management of access to cardiac surgery in the Brazilian Unified Health System at a university hospital in Campinas: pre-post analysis, 2013-2019 - Silvia Thomas Antunes; Viviana Aparecida de Lima; Ivan Lira dos Santos; Rafaela Amadio Miguel; Gustavo Calado de Aguiar Ribeiro; Elisa Teixeira Mendes (Epidemiologia e Serviços de Saúde)
Abstract Objective To compare the pre- and post-implementation periods of a program to manage access to cardiac surgery for users of the SUS (Brazilian Unified Health System) in terms of surgical waiting time. Methods This is an observational and retrospective study, which analyzed three years before and four years after the implementation of this program. Variables such as length of hospital stay, waiting time in the surgical queue and infection rate of users who underwent elective cardiovascular surgery in the SUS were evaluated. Results There was a significant reduction in waiting times in the queue of 97.50 days in the pre-intervention period (95% confidence interval – 95%CI 79.00; 120.30) and 52.50 days (95%CI 44.40; 63.20) in the post-intervention period. There was a trend towards a reduction in the average hospital stay and an increase in the number of surgeries performed. Conclusion The implementation of the management program reduced the waiting time for cardiac surgery in the SUS (Brazilian Unified Health System).